Ultrastructural features of the lining epithelium of the vas deferens of Agouti paca - Orsi, A. M. [UNESP]; Simoes, K.; Fernandes Machado, M. R. [UNESP]; Da Cruz, C. [UNESP]; Fantin Domeniconi, R. [UNESP] (My University, 2006)
The epididymal epithelium of Agouti paca, a wild South American rodent, was basically formed by principal and basal cells. Principal cells were closely related to processes of adsorptive endocytosis, phasefluid endocytosis and also secretion originating from their cytoplasmic ultrastructural features. Principal cells were also characterized by the presence of vesicles of several shapes, sizes and internalized content occurring in smaller pits, pale small vesicles next to the apical brush border of microvillus, as well as coated vesicles, smooth surface vesicles and great vesicles. Multivesicular bodies, endosomes and lysosomes were mainly observed in supranuclear position. Moreover, presence of an apocrine secretory process was demonstrated by the occurrence of apical cytoplasmic expansions projecting into the vas deferens luminal compartment. Basal flattened cells without luminal surface contact occurred next to the basement membrane of the ductus, and did no exhibit special ultrastructural features.
Keywords: Epididymidis epithelium; Histophysiokgy; Ultrastructure; Wild rodent; animal; cytoplasm; endocytosis; epithelium cell; male; methodology; physiology; rodent; transmission electron microscopy; ultrastructure; vas deferens; wild animal; Animals; Animals, Wild; Cytoplasm; Endocytosis; Epithelial Cells; Male; Microscopy, Electron, Transmission; Rodentia; Vas Deferens; Agouti paca